REKONSTRUKSI PARADIGMA PEREMPUAN DALAM POLITIK (STUDI PEMAKNAAN HUKUM TERHADAP TEKS KETERWAKILAN PEREMPUAN DALAM PARLEMEN) - Endrawati, SH., MH, Lucky (EGALITA, 2008)
Democracy transition era which is happening in Indonesia recently, inspires wider demand of the improvement of political opportunity for all its citizens. It opens a leeway for women to posit themselves in political arena which has been legitimated and been accommodated by UUD 45. As the irony of the fact, there is a complicated interest and tight negotiation process between the dominant political ideology and the developing inspiration. In determining people's representative in the parliament in each of political parties, women are still holdding the lowest number. It indicates that there is still menâ€™s hegemony to â€œconquereâ€ the parliament. This ironical fact of political rights is not only due to the various interpretation of 30% regulation of womenâ€™s proportion but also the weaknesses of law enforcement in politics. The lowest level of law enforcement in politicsÂ  results in orientation of political feminism bias which echoes gender equality and equity. It is not easy to give meaning and interpretation to regulation texts of womenâ€™s 30% proportion in the parliament. Hence, it should be looked holistically, responsibly as well as progressively.Kata kunci : paradigma, teks, keterwakilan perempuan